Psychometric properties of the Persian version of the design thinking mindsets questionnaire - Vaqari Zamharir, Zahra; Karami, Morteza; Jamali, Jamshid; Saeidi Rezvani, Mahmoud (Frontiers in Education, 2025)
PurposeLearners with a design thinking mindset can improve several levels of cognitive processes, such as thinking skills, research skills, learning skills, self-exploration, creativity, and innovation. The present study was carried out with the aim of translation, cultural adaptation, and evaluation of the psychometric characteristics of the design thinking mentality questionnaire for Iranian students.MethodsA four-step study was performed in the current work. After translating the questionnaire using the translation-re-translation method, content validity was examined. The content validity ratio (CVR) and content validity index (CVI) were assessed using constructing construct validity factor analysis. Then, the translated questionnaire was presented to 300 students. Reproducibility (stability) was evaluated using the intracluster correlation coefficient. The internal consistency was evaluated using Cronbach’s alpha.ResultsThe results of confirmatory factor analysis (CFA) confirmed the structure of eight factors (risk tolerance, human-centeredness, holistic view, problem reframing, teamwork, experiment, abductive thinking, and creative self-confidence) with 37 questions. Cronbach’s alpha coefficient for the whole instrument was 0.925, and the intracluster correlation coefficient (ICC) was 0.842 at a significance level of p = 0.001, which indicates the stability and good reproducibility of the tool.ConclusionThe findings generally, the findings support the validity and reliability of the Persian version of the design thinking mentality questionnaire. This means that the instrument can be used to measure the design-thinking mentality.